STUDY OF EUPHEMISM IN ONLINE MASS MEDIA NEWS KOMPAS.COM AND IT'S IMPLEMENTATION AS TEACHING MATERIAL FOR NEWS TEXTS - Randila Hasna Alifah, - (2021)
This research found on the development of the mass media who have switched to the online form. The mass media has a who space and is very fast to provide information. Today's online mass media have a high role in the socialization process and the meaning of new terms emerging in the news. It is possible to increase the reader's interest in application language that is less subtle and inappropriate in the notification. Based on this, it is necessary to study the switch of more subtle terms or so-called euphemisms to help make information boundaries so selective in language use. This study uses a descriptive qualitative method. The source of the data for this research is the news on Kompas.com published in June 2021. The data collection technique we using listening, reading, and note. Data analysis used descriptive techniques and informal presentation of results. Validation in this study is semantic validity and interrater reliability. The results showed that there were 49 euphemism data. The data found are words, phrases, and clauses. Judging from the types of references found, namely objects, diseases, activities, events, characteristics, and circumstances. The euphemisms on Kompas.com news have the function of smoothing speech to appreciate, attract sympathy, and maintain a good name. There is also a refinement of speech for unpleasant things, bad things, scary things, sad things, and legal actions according to the context of the sentence. Based on the results of this study, news with the term euphemism the considered to have a value to be used as teaching material for news texts for class VIII that are relevant to the distribution of information among junior high school students.